Katakan Tidak Pada Bullying: Ceria Bersama Mewarnai Dunia Kecil Mereka - Gustiawan, Deni; Risnawati, Henny; Santosa, Bambang; Sari, Hastuti Indra; Zulmita, Zulmita; Rahmadiana, Rahmadiana; Kasusilaningrum, Tyas; Fikri, Fikri (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2025)
This activity was carried out by lecturers and HIMMA (Management Student Association) from the Swadaya Business and Communication Institute (SWINS) at Rumah Yatim Duren Sawit, East Jakarta, with the theme